Using cloud computing to support higher education in networks and systems. (2016) - Liu, Jianwei; Fu, Yunhui; Martin, Jim
Virtual machine (VM) technology is widely used in higher education to support pedagogy and research. However, without a standard platform for managing VM technology, VM-based infrastructure is likely to be acquired and deployed in an ad-hoc manner. The virtual computing lab (VCL) system is an open source cloud computing platform developed specifically to support higher education. The main goal of VCL is to make available dedicated, custom compute environments to users. We built a small VCL cloud and trialed its use to support several networking courses offered in the School of Computing at Clemson University during the 2013/2014 academic year. In this paper, we summarise the trial and provide results and conclusions. We found that well provisioned PCs might support up to ten VMs however when subject to peak loads, the system is not able to support accurate and reproducible network experiments.